Social legislation in Poland : an informal talk given at the Allied Lawyers' Foyer, on the 15th of May, 1944 - Bloch, J. (London : The Polish Lawyers' Association in the United Kingdom, 1944)
Bibliotheek Camille Huysmans
Engels
Brochure
Keywords: sociale wetgeving; sociale zekerheid; Polen